Chemical recycling of poly(ethylene terephthalate). Application to the synthesis of multiblock copolyesters - F. Malek; A. El Mejjatti; T. Harit; A. Riahi; R. Khiari; I. Bouabdallah (eXPRESS Polymer Letters)
The chemical recycling of the poly(ethylene terephthalate), (PET), has been successfully carried out by glycolysis in the presence of bis (2-hydroxyethyl) terephthalate (BHET) resulting in the formation of hydroxytelechelic oligomers. These oligomers were then treated with carboxytelechelic poly(ε-caprolactone) oligomers of Mn = 2300 and Mn = 730 g•mol–1 molecular weight, in the absence or presence of the titanium tetrabutyloxide (Ti(OBu)4) as a catalyst to get multiblock copolyesters. The chemical structure of the synthesized copolyesters was investigated by size exclusion chromatography (SEC) and proton Nuclear Magnetic Resonance (1H NMR) spectroscopy. Moreover the differential scanning calorimetry (DSC) was used to explore their thermal properties. The ester-ester interchange reaction was observed between the two oligopolyesters, was studied and discussed in detail.